Mapping the availability of ayurveda and other complementary medicine services centres in Nepal. (2018)
SUMMARY: Traditional and Complementary Medicine (T&CM) comprises of wide spectrum of practices to prevent and cure diseases .The terms like complementary, alternative, non-conventional medicine are homogenously used in different countries in reference to traditional medicine. The classification of practices and definitions of Traditional Medicine varies in different countries depending on the availability, accessibility, cultural and historical significance, and regulations. In Nepal T&CM is implied as Ayurveda and Alternative medicine. National Health Policy 2074 defines other Alternative system as Yoga, Naturopathy, Sowa Rigpa, Homeopathy, Unani, Traditional Chinese Medicine, and traditional medicine and practices. There isvery limited knowledge about institutions providing T&CM service, Information on what conditions do patients usually consult for at T&CMs, type of services they provide, exact location of the particular kind of services and number of T&CM providing institutions inside Kathmandu Valley will be beneficial to service seekers This study aims to collect information on the availability of Traditional and Complementary service facilities through GIS mapping to provide a complete picture of spatial distribution of facilities in Nepal. The study was conducted in two phases; initially data was collected from Kathmandu valley including Kathmandu, Bhaktapur and Lalitpur.In the second phase we collected the data from all over Nepal. For the purpose of data collection, we included the following system of T&CM practices: Ayurveda, Homeopathy, Naturopathy, Acupuncture and Amchi(Sowa Rigpa). Herbal medicine centers were excluded from the study. For assessing information about availability of the services on those centers, a semi structured questionnaire was designed. Similarly, for location information Garmin GPS device was used. The majority of complementary medicine centers were practicing Ayurveda followed by Homeopathy. The third most practiced system was Acupuncture. Acupuncture was mostly practiced in conjunction with Ayurveda or Naturopathy. Amchi was least practiced system in Nepal. A rigorous research on challenges and opportunity and identify gaps associated with Ayurveda and Complementary Medicine practices will assist in future development of this system.